Cattleya mireileiana, a new species of Orchidaceae (Laeliinae) from the Southern Espinhaço Complex, Minas Gerais State, Brazil - Menezes, Euler Da Luz Fernandes; Giordani, Samuel Cunha Oliveira; Mendes, Jone Clebson Ribeiro (Phytotaxa, 2022)
This study describes and illustrates Cattleya mireileiana (Orchidaceae: Laeliinae), a new species endemic to the Southern Espinhaço Complex near Diamantina, Minas Gerais State, Brazil, where it was found in a few isolated rocky outcrops, sharing habitat with Cattleya rupestres. It is close to three other species: Cattleya bradei, C. briegeri, and C. cruziana. However, the new species differs in the number of nodes present in the pseudobulb components, the size of the diameter, the scent of the flowers and the time of flowering. In addition, its flowers have two unique chromatic characteristics that distinguish it from all other species with yellow flowers in the Parviflorae series: the color of the carinae and the whitish area at the base of the petals and sepals. We provide a detailed morphological description, a distribution map, in situ photographs, and compare it with similar species. We assessed its state of conservation as data deficient  (DD), as the only know population consists of at least 150 mature individuals and is outside of an environmentally protected area.